Survey of Some Medicinally Important Leafy Vegetables in Rupandehi District of Western Nepal - Singh, Anant Gopal (International Journal of Applied Sciences and Biotechnology, 2015)
Green leafy vegetable is a major source of vitamins and micronutrients for people using only vegetarian diets rich in carbohydrates. In remoterural settlements where vegetable cultivation is not practiced and market supplies are, not organized, local inhabitants depend on indigenousvegetables, both cultivated in agricultural fields or kitchen gardens and wild for enriching the diversity of food. Knowledge of such food ispart of traditional knowledge, which is largely transmitted through participation of individuals of households. The purpose of this study was todocumentation of plants used as vegetables by the people of Rupandehi district of Lumbini zone of western Nepal. This paper revealed total51 plant species belong to 45 genera under 32 Families of vascular plants. Out of 32families, 24 families belong to dicot, 4 families to monocotand 4 families belong to ferns. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12220 Int J Appl Sci Biotechnol, Vol. 3(1): 111-118